Symptoms associated with button batteries injuries in children: An epidemiological review. Issue 12 (December 2015) - Buttazzoni, Elisa; Gregori, Dario; Paoli, Bibiana; Soriani, Nicola; Baldas, Solidea; Rodriguez, Hugo; Lorenzoni, Giulia
Abstract: Objectives: To provide an epidemiological framework of symptoms related to Foreign Body (FB) injuries due to Button Battery (BB). Methods: Data on BB ingestion/inhalation have been obtained from the ButtonBatteryDB. The ButtonBatteryDB is a database collecting information on BB injuries in children (0–18 years of age). Data on 348 BB injures have been derived from the Registry of Foreign Body Injuries "Susy Safe" (269 cases) and from published scientific literature reporting case reports of FB injuries (79 cases). Results: Most of injured children were male and BBs were found more often in the mouth/esophagus/stomach (ICD935) and in the nose (ICD932). Analyzing symptoms related to BB located in the esophagus/mouth/stomach, we found that children had higher probability of experiencing dysphagia (30.19%, 95% C.I. 17.83–42.55), fever and cough (26.42%, 95% C.I. 14.55–38.28), compared to the other symptoms. Referring to the probability that symptoms occurred simultaneously, fever and cough are more likely (3.72%, 95% C.I. 1.0–6-43) to jointly showing up in children with BB in mouth/esophagus/stomach (ICD935), followed by fever and dysphagia (2.66%, 95% C.I. 0.36–4.96) and by fever and irritability/crying, fever and drooling, dysphagia and irritability/crying (2.13% C.I. 0.00–4.19, 95% C.I.) Conclusions: These findings provide new insight in clinical presentation of BB injuries: the identification of unique patterns of symptoms related to BB injuries is useful to perform an early diagnosis (and to guarantee a prompt medical reaction), also when the injury is un-witnessed.